2011
DOI: 10.1080/17461391.2011.638935
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between different loads in resisted sprints, half‐squat 1 RM and kinematic variables in trained athletes

Abstract: Resisted sprint running is a common training method for improving sprint-specific strength. It is well-known that an athlete's time to complete a sled-towing sprint increases linearly with increasing sled load. However, to our knowledge, the relationship between the maximum load in sled-towing sprint and the sprint time is unknown, The main purpose of this research was to analyze the relationship between the maximum load in sled-towing sprint, half-squat maximal dynamic strength and the velocity in the acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
2
17
1
1
Order By: Relevance
“…The results showed that an increase in loads led to a decrease in sprint performance over 20 and 30 m when athletes ran under different conditions (10%, 15%, and 20% Bm). Similar results may be found in previous studies ( Alcaraz et al, 2009 ; Cronin et al, 2008 ; Keogh et al, 2010 ; Letzelter et al, 2005 ; Linthorne, 2013 ; Lockie et al, 2003 ; Martínez-Valencia et al, 2014 ; Maulder et al, 2008 ; Murray et al, 2005 ). Lockie et al (2003) found that loads of 12% and 32% Bm decreased velocity during 15 m acceleration to 91% and 76%, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results showed that an increase in loads led to a decrease in sprint performance over 20 and 30 m when athletes ran under different conditions (10%, 15%, and 20% Bm). Similar results may be found in previous studies ( Alcaraz et al, 2009 ; Cronin et al, 2008 ; Keogh et al, 2010 ; Letzelter et al, 2005 ; Linthorne, 2013 ; Lockie et al, 2003 ; Martínez-Valencia et al, 2014 ; Maulder et al, 2008 ; Murray et al, 2005 ). Lockie et al (2003) found that loads of 12% and 32% Bm decreased velocity during 15 m acceleration to 91% and 76%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…As a result, Murray et al (2005) suggested that one test would produce valid data. Previous studies that had analyzed the effect of sled towing on sprint performance also recorded one sprint for different load conditions ( Cronin et al, 2008 ; Martínez-Valencia et al, 2013 ; Martínez-Valencia et al, 2014 ). As a result, this procedure was adopted in the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All them keep the location in the treadmill and the position of the belt (between waist and hip). This allowed us to reproduce in the laboratory conditions similar to field tests, as in prior studies 23 24 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding RST loads, the present findings demonstrated that JHs in SJ, but not CMJ, were moderately correlated to L10% and L30%, but not to L50%, and this association decreased as a function of load increment. Previous research [36] reported that the increase in loads involves a decrease in sprint performance over 20 m when athletes sprinted under different conditions (unresisted and towing sleds with loads between 5% and 30% BM). The present findings suggest that, when sprinting with heavier loads, the variables that correlate with performance are different than when sprinting under unloaded conditions.…”
Section: Discussionmentioning
confidence: 99%